ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) DENGAN METODE FITOREMEDIASI PADA KAWASAN PERCETAKAN DI KOTA MEDAN - Juwairiah Juwairiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2021)
This study aims to determine the content of the heavy metal lead (Pb) in water spinach (Ipomoea aquatca) in the printing area of Medan City. Phytoremediation is a remediation method that relies on the role of plants to absorb, degrade, transform and mobilize heavy metal pollutants, in this case using water spinach plants. This research is descriptive by taking samples randomly, meaning that water spinach plants (Ipomoea aquatica) were taken randomly from the printing area in Medan City. So that the water spinach (Ipomoea aquatica) in the printing area in Medan is still safe for public consumption. The highest levels of Lead (Pb) in water spinach (Ipomoea aquatica) are obtained from point 1 on Jalan Masjid Kesawan which is 0.04497mg / kg while the lowest levels of Lead (Pb) are at point 2 which is on Jalan Jamin Ginting Padang Bulan that is 0.02273 mg / kg.